Effect of in ovo-fed amino acids on muscle and liver metabolome of broiler chickens at 24 h post-hatch - Yehia, Moustafa; Alfonso-Avila, Angel Rene; Allard Prus, Jean-Michel; Ouellet, Véronique; Alnahhas, Nabeel (Frontiers in Physiology, 2025)
In ovo administration of amino acids has been shown to alleviate the adverse effects of heat stress on broiler chickens during the finisher phase. However, their specific influence on thermogenic organs in the early post-hatch period is not fully understood. Therefore, the aim of the present study was to explore and investigate the effects of in ovo-fed amino acids on amino acid metabolism in the liver and muscle of one-day-old broiler chicks. To achieve this, breast muscle and liver samples were taken from six randomly selected chicks per experimental group and subjected to a targeted metabolomic analysis. The experimental groups included a control group injected with 52 µL of sterile diluent/egg (CTRL), a group injected with 3.0 mg of L-Met + 2.0 mg of L-Cys/egg (T1), and a group injected with 0.4 mg of L-Leu + 1.6 mg of L-Met + 1.6 mg of L-Cys/egg (T2). The Sparse Partial Least Square – Discriminant Analysis (sPLS-DA) showed that T1 and T2 had very similar metabolomic profiles. Consequently, data from T1 and T2 were merged into a single group (Injected) for statistical analysis. Compared to CTRL, multiple pathways were significantly enriched in the muscle and liver of the Injected group. These enriched pathways included those involved in the metabolism of cysteine and methionine (FDR = 0.01), glutathione (FDR < 0.001), histidine (FDR = 0.01), taurine (FDR = 0.01), glycine, serine, and threonine (FDR = 0.01) as well as the pathway of arginine biosynthesis (FDR = 0.03). Moreover, only four muscle metabolites: homocysteine (r = −0.63, P = 0.03), S-Adenosyl-homocysteine (r = −0.62, P = 0.03), phosphocholine (r = 0.50, P = 0.01), and betaine (r = 0.52, P = 0.004), as well as four liver metabolites: phenyl pyruvic acid (r = 0.55, P = 0.02), dimethylglycine (r = 0.55, P = 0.03), phenylalanine (r = 0.50, P = 0.02), and alpha-aminobutyric acid (r = −0.53, P = 0.02) were significantly correlated with the rectal temperature of sampled chicks, suggesting a role of these metabolites in thermoregulation. In conclusion, the in ovo feeding of amino acids on embryonic day 18 was associated with the enrichment of pathways directly or indirectly involved in the response of the antioxidant defense system to oxidative stress in the liver and muscle tissues.